Karyotypic analysis of Crucian carp, Carassius carassius (Linnaeus, 1758) from cold waters of Kashmir Himalayas - Gousia jan; Asim Iqbal Bazaaz; Azra Shah; Saima Andleeb; Irfan Ahmad; Duedana Qazi; Oyas Asimi; Bilal A. Bhat; Anayitullah Chesti (Caryologia, 2023)
Carassius carassius (Linnaeus, 1758) is an exotic fish to Kashmir, locally known as “gang gad” and commonly called as “crucian carp”. It belongs to family Cyprinidae. The present study aimed to identify the chromosome number of the Carassius carassius and to optimize the colchicine concentrations (0.01%, 0.025%, and 0.05%) and hypotonic treatment timings (25, 35, and 45 minutes) for the chromosome preparation in Carassius carassius in order to obtain the highest number of clear and identifiable metaphasic chromosomal spreads. Data collected was analyzed and the means of each treatment was compared. The findings of the present study indicated that there was a significant influence of colchicine concentration, hypotonic timings as well as colchicine concentration× hypotonic timings (P<0.01) on the number of metaphase chromosome spreads. Furthermore a significant (P<0.01) strong positive correlation obtained between colchicine concentrations, hypotonic timings and the number of metaphase chromosome spreads. The findings of the present study recommends further research into chromosomal modification techniques such as fish polyploid production, gynogenesis, androgenesis, and inter or intra-species hybridization is needed to generate unique and good inbred lines in aquaculture.